Advances in Magnetically Controlled Medical Robotics: A Review of Actuation Systems, Continuum Designs, and Clinical Prospects for Minimally Invasive Therapies - Tiantian Kong; Qitong Zheng; Jiarong Sun; Chunxiao Wang; Huibin Liu; Zhizheng Gao; Zezheng Qiao; Wenguang Yang (Micromachines)
Magnetically controlled micro-robots hold immense potential for revolutionizing advanced medical applications, garnering significant research interest. This potential is underscored by the dual focus on magnetic control systems—both as driving forces and manipulation field sources—and magnetic continuums that have demonstrated clinical therapeutic efficacy. This comprehensive review delves into the actuation characteristics of permanent magnet systems, electromagnetic systems, and commercially available magnetic control systems. It also explores innovative designs of magnetic wires and tubes serving as continuum structures and investigates the variable stiffness properties of magnetic continua, informed by material and structural attributes. Furthermore, the discussion extends to their prospective roles and future applications within the medical realm. The objective is to elucidate emerging trends in the study of magnetic control systems and magnetic continua, marked by an expanding operational scope and enhanced precision in manipulation. By aligning these trends with clinical challenges and requirements, this review seeks to refine research trajectories, expedite practical implementations, and ultimately advocate for minimally invasive therapies. These therapies, leveraging magnetic control systems and magnetic continuums as cutting-edge treatment modalities, promise transformative impacts on the future of healthcare.